Bismuth(iii)-catalyzed bis-cyclization of propargylic diol-esters: a unified approach for the synthesis of [5,5]- and [6,5]-oxaspirolactones - Kambale, Digambar A.; Borade, Balasaheb R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2021)
Herein we disclose an unprecedented intramolecular cascade strategy for the construction of alpha,beta-unsaturated [5,5]- and [6,5]-oxaspirolactones that capitalizes on the pi-electrophilic Lewis acid-catalyzed 5-exo-dig or 6-exo-dig mode of cyclization of propargylic diol esters, followed by dehydration and spirolactonization steps. Moreover, semi-protected substrates also delivered the respective oxaspirolactones with the same ease and in appreciable yields under optimal reaction conditions.

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus